Having a hearing test - Parker, Victoria (Toronto CNIB, 2015)
Learn about what happens when you get your hearing tested. Includes equipment, where the test may happen, why you need one, and tips on keeping your ears healthy. Grades K-3. 2011
The world around us
a gift from book africa
1 2 13 15
Keywords: Hearing disorders -- Diagnosis -- Juvenile literature; Hearing disorders